Adsorption of Bisphenol A on KOH-activated tyre pyrolysis char. Issue 1 (February 2018) - Acosta, R.; Nabarlatz, D.; Sánchez-Sánchez, A.; Jagiello, J.; Gadonneix, P.; Celzard, A.; Fierro, V.
Graphical abstract: Highlights: KOH activation of tyre pyrolysis char produced high surface activated carbons (ACs). KOH activated char adsorbed more Bisphenol A (BPA) than commercial ACs. BPA adsorption on activated char was an exothermic process. BPA adsorption kinetics followed a pseudo-second order model. ACs synthesis would improve the economic balance of pyrolysis oil production. Abstract: An activated carbon (AC) with a specific surface area of 700 m 2  g −1 was prepared by KOH activation of tyre pyrolysis char (TPC) and tested to remove Bisphenol A (BPA) from aqueous solutions. BPA adsorption on this AC was evaluated by studying both the adsorption isotherms at three different temperatures and the decrease of BPA concentration with time, in order to determine the thermodynamic and the kinetic parameters, respectively. The results were compared with those obtained with pristine TPC and with a multipurpose commercial activated carbon (CAC) recommended for BPA adsorption. The present KOH-activated TPC showed a great potential to adsorb BPA with a monolayer capacity as high as 123 mg g −1, higher than that of the CAC used as a reference. BPA adsorption equilibrium data were fitted using different isotherm models with two or three parameters, and the best fitting models were those of Langmuir and Radke-Prausnitz. BPA adsorption was an exothermic process, and the adsorption capacity decreased with increasing temperature. The adsorption kinetics of BPA was adequately described by a pseudo-second order model.